Hubungan tingkahlaku kepimpinan dengan komitmen kerja di NGO yang tidak berasaskan keuntungan - Siti Marhamah, Bte Abd Ghapar. (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study aims to identify the relationship between leadership behaviors with organizational commitment at the non-profit NOD. Leadership behaviors stand as independent variable that was divided into two which were task-oriented and relation-oriented, while organizational commitment stand as a dependent variable. This study involved 45 respondents which were subordinates at chosen NOO 's around Kuching that are Sarawak Breast Cancer Association, Sarawak Thalassemia Association, Sarawak Ophens Association, and Angkatan Zaman Mansang (AZAM). All respondent were selected randomly. The instrument that has been used was the adapted version of Stogdill, 1975 Questionnaire (LBDQ) and Mowday, Steers and Porterl979, (OCQ). Data were analysed using Statistical Package for Social Sciences (SPSS) Version 12.0. The relationship between leadership behaviors and organizational commitment were analysed using Pearson Correlation while Multiple Linear Regressions had been used to analyse dominant leadership behavior. Analysis shows that there were a weak relationship between task-oriented leadership behavior and organizational commitment, (p = 0.000 and r = -0.174). While there was a strong relationship between relation-oriented leadership behavior and organizational commitment, (p =0.000 and r = -0.75)1. Relation-oriented leadership behavior found as a dominant factor which result 53% (R2 = 0.531)